Mikropropagasi Tanaman Stroberi (Fragaria sp.) melalui Induksi Organogenesis - SAPUTRA, I MADE CHRISTIAN ADHI; DWIYANI, RINDANG; YUSWANTI, HESTIN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.5, No.4, Oktober 2016, 2016)
Mikropropagation Plant Strawberries ( Fragaria sp.) Through Induction of Organogenesis Problems for farmers strawberry in Bali are the difficulty of get healthy strawberries  seeds a with prices are relatively cheap. Micropropagation method is ways to multiplay seeds for solving the problem. Research aims to understand the influence of concentration ZPT NAA + BAP to organogenesis on explant leaves strawberries in vitro. Experiment arranged using a Randomized Block Design (RBD). Medium the base used is MS medium with adding of 2 gL - 1 of activated charcoal, and 0.1 ppm NAA. As the treatment is BAP with concentration of 5 ppm, 10 ppm and 15 ppm with 5 replications. The results showed that the use of 0,1 ppm NAA + 15 ppm BAP most effective in deflection (3,0 DAP) with the percentage of 90,00%. The use of the NAA 0,1 ppm + 15 ppm BAP also most effective in a time of swelling (7,6 DAP) with the percentage of 82,95 % , while only the use of the NAA 0,1 ppm + 5 ppm BAP that will be capable of eliciting shoots at 23 DAP time.
Keywords: Micropropagation; Strawberries; Organogenesis; Exsplants and in vitro